Hormonersatztherapie bei prämaturer Ovarialinsuffizienz: Rationale, Indikation und Dauer - Strowitzki, Thomas (Der Gynäkologe, 2017)
BackgroundPremature ovarian insufficiency (POI) involving a loss of estrogen production is a life-determining situation for affected women, leading to infertility and chronic sequelae for women’s health. This requires long-term strategies for hormone replacement over years or even decades.ObjectivesThis review pays special attention to the risks, benefits, administration and treatment duration of hormonal replacement, all of which differ substantially from the situation in natural menopause.Results and discussionThere is wide consensus that hormone replacement therapy is indicated in women with POI if potential contraindications are excluded. The transdermal cyclic approach is considered the first choice. In women requiring definitive contraception, estrogen replacement can be successfully performed using hormonal oral contraceptives. Replacement therapy should be continued at least until the age of natural menopause, i.e., early 50s. Thereafter, hormone therapy follows the standard recommendations for postmenopausal women suffering from climacteric symptoms.